Assessment of metalloproteinase inhibitors clodronate and doxycycline in the neutralization of hemorrhage and coagulopathy induced by Bothrops asper snake venom - Rucavado Romero, Alexandra (2008)
Snake venom metalloproteinases (SVMPs) play a prominent role in the local and systemic manifestations of viperid snakebite envenomations. Thus, the possibility of using metalloproteinase inhibitors in the treatment of these envenomations is a promising therapeutic alternative. This study assessed the ability of two metalloproteinase inhibitors, the biphosphonate clodronate and the tetracycline doxycycline, to inhibit proteolytic, hemorrhagic, coagulant and defibrinogenating effects of Bothrops asper venom. Both compounds were able to inhibit these activities, at concentrations in the mM range, when incubated with venom prior to testing. However, when inhibition of hemorrhage was assessed in assays involving independent injection of venom and drug, inhibition was poor, even when these compounds were injected immediately after envenomation. These findings support the concept that the effectiveness of compounds, such as clodronate and doxycycline, whose inhibitory action on SVMPs is based on zinc chelation alone, is limited, and stress the view that more specific molecules are required for an effective inhibition of SVMPs in vivo.